Long-term site fidelity and seasonal abundance estimates of common bottlenose dolphins (Tursiops truncatus) along the southwest coast of Florida and responses to natural perturbations - Bassos-Hull, Kim; Perrtree, Robin M.; Shepard, Christine C.; Schilling, Stephanie; Barleycorn, Aaron A.; Allen, Jason B.; Balmer, Brian C.; Pine, William E.; Wells, Randall S. (J. Cetacean Res. Manage., 2023)
Information characterising site fidelity and abundance for common bottlenose dolphins (Tursiops truncatus) along the southwest coast of Florida is important for defining stock structure for management purposes. Long-term site fidelity and ranging patterns of bottlenose dolphins in Charlotte Harbor and Pine Island Sound, Florida were investigated using photo-ID data collected during 566 boat-based surveys from 1982 through 2007. Seasonal abundance estimates were generated from seven multi-week field seasons during 2001 through 2006, before and after a major hurricane and red tide event occurred in the area. In total, 1,154 distinctive dolphins were identified up to 34 times each with 84% of individuals resighted on more than one day. Multiple year residency rates were high with 81% of dolphins sighted in at least two years and 30% over ten or more years. Seventy-six percent of individuals with sightings on two or more days were observed in both summer and winter. Of 249 dolphins sighted on ten or more days in the study area, 83% were never observed outside the study area, indicating strong site-fidelity. Two years after a devastating Category 4 hurricane in 2004 and following two years of Karenia brevis harmful algal blooms, 94% of dolphins were observed in the same region within the study area and abundance estimates remained stable. Documenting range and site fidelity patterns of individuals over long periods of time is helpful for characterizing population structure and for examining changes attributable to environmental factors and perturbations such as hurricanes, harmful algal blooms and climate change.